2016
DOI: 10.2147/rrfu.s63233
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided high-intensity focused ultrasound treatment of uterine fibroids

Abstract: Uterine fibroids are benign, encapsulated uterine tumors, representing the most common reason for hysterectomy in premenopausal women. High-intensity focused ultrasound (HIFU; also known as focused ultrasound surgery) is a noninvasive technique leading to tissue heating in a centered focus, inducing a thermal tissue necrosis. Magnetic resonance-guided HIFU (MR-HIFU; also know as MR-guided focused ultrasound surgery) allows to allocate the uterine fibroids as well as to evaluate whether these are accessible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Studies have shown that quality of life after hysteroscopic myomectomy was signi cantly better than after laparoscopic myomectomy due to shorter operative duration, less intraoperative bleeding, and shorter hospitalization [18]. Other uterine sparing minimally invasive techniques available for treating submucosal broids include uterine artery embolization (UAE) [19], hysteroscopic myomectomy after UAE [20], and transvaginal radio-frequency myolysis [21,22] and magnetic resonance-guided high intensity focused ultrasound (MR-HIFU) [23,24]. UAE showed improvement in symptom score and quality of life score outcomes when associated with heavy bleeding and submucosal leiomyoma location [25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that quality of life after hysteroscopic myomectomy was signi cantly better than after laparoscopic myomectomy due to shorter operative duration, less intraoperative bleeding, and shorter hospitalization [18]. Other uterine sparing minimally invasive techniques available for treating submucosal broids include uterine artery embolization (UAE) [19], hysteroscopic myomectomy after UAE [20], and transvaginal radio-frequency myolysis [21,22] and magnetic resonance-guided high intensity focused ultrasound (MR-HIFU) [23,24]. UAE showed improvement in symptom score and quality of life score outcomes when associated with heavy bleeding and submucosal leiomyoma location [25].…”
Section: Discussionmentioning
confidence: 99%
“…HIFU ablation is, however, not suitable in some situations such as (a) Bowel adhesions found in the acoustic pathway, which will increase the risk of bowel injury [19,26]. (b) The lesion of adenomyosis is too small, because adenomyoma is without a pseudocapsule, and the ablation heat may diffuse and spread to the uterine serosa or endometrium, causing damage to bowel, bladder or endometrium.…”
Section: High Intensity Focused Ultrasound (Hifu) Ablation Treatmentmentioning
confidence: 99%
“…Therefore if the lesion is too small, i.e., with the lesions in the uterine wall together measured less than 3 cm, HIFU ablation might not be applicable [19]. (c) Severe abdominal keloid scars which can affect ultrasound penetration and lead to skin or keloid burn [19,26].…”
Section: High Intensity Focused Ultrasound (Hifu) Ablation Treatmentmentioning
confidence: 99%